Nursing Care For Patients With Post Debridement Diabetic Ulcers With Moist Wound Healing Innovation Interventions At General Ahmad Yani Hospital, Metro City - Hartanti, Novi; Wardoyo, Eko; Sugiarto, Sugiarto (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Diabetes is one of the problems caused by chronic metabolic disorders characterized by high sugar levels accompanied by metabolic disorders of carbohydrates, lipids, and proteins as a result of insufficient insulin function. The purpose of this study was to determine the effect of moist wound healing on post debridement diabetic ulcers. Descriptive research with a case study approach in multiple cases. Method: Data collection methods used surgical nursing care assessment sheets and Bates-Jensen Wound Assessment Tools (BWAT) wound assessment sheets. The study used 2 patients with the same criteria Result: The results of nursing care obtained in patient 1 are tissue integrity disorders, instability of blood glucose levels, and knowledge deficits. Patient 2 had problems with tissue integrity disorders, physical mobility disorders, and knowledge deficits. After nursing care was carried out, it was found that in patient 1 there was a decrease in wound score from 40 to 37 after moist wound healing treatment. Instability of blood sugar levels has not been resolved, patients get insulin therapy. The knowledge deficit was resolved on the second day. In patient 2, there was a decrease in wound score from 37 to 35 after moist wound healing treatment. Physical mobility disorders have not been resolved and the knowledge deficit was resolved on the second day. Conclusion: Suggestions for patients and families can use the booklet media made by researchers as a guide for wound care, wound observation, diabetic diets, and drug compliance.